Analisis Kesulitan Pelafalan Makharijul Huruf Dalam Membaca Al-Qur’an Mahasiswa Prodi Pendidikan Agama Islam - Muhammad Ihsan; Indah Muliati (Universitas Pahlawan Tuanku Tambusai, 2024)
As Muslims, the Qur'an should be the main reference in various fields of life including in educational activities and the formation of the personality of Muslims. Islamic students should always interact with the Qur'an either by reading, listening, memorizing, understanding the Qur'an and practicing the Qur'an as a manhajul hayah and preaching it to the community. This research uses a qualitative method with a qualitative descriptive approach. Data collection techniques were carried out by observation, interviews and documentation. Data analysis uses data reduction, data presentation and conclusion making. The results of the study obtained by students show difficulty in pronouncing hijaiyyah letters according to makharijul huruf, according to the harakat or short length and still have difficulty in reading the Qur'an according to the rules of tajweed. The factors that cause difficulties in reading the Qur'an of students are the lazy learning factor of the students themselves and the learning factors received are different between students who have different backgrounds in previous education who pay less attention to reading the Qur'an. Then, the surrounding environment both in the family and the student friendship environment which is still lacking in paying attention to the reading of the student's Qur'an. The solution carried out on the difficulty of reading the Qur'an by students, namely, by learning to study the Qur'an using the read and write method and repeating